Evaluate the Compliance of Diabetes Patients in Taking Medication Diabetes Mellitus in Puskesmas Between Makassar City - Zulfiah, Zulfiah; Patandung, Gerfan; Mildawati, Mildawati (Politeknik Sandi Karsa, 2022)
Diabetes mellitus is a disease in which the sufferer's body cannot automatically control the level of sugar (glucose) in the blood. In a healthy body, the pancreas releases the hormone insulin, which is responsible for transporting sugar through the blood to the muscles and other tissues to supply energy. Glucose normally circulates in a certain amount in the blood. Glucose is formed in the liver (hepar) from the food consumed. The purpose of this study was to determine the level of adherence of diabetic patients in taking DM medication at the Antara Public Health Center in Makassar City. The method used in this research is descriptive, namely research that includes surveys with data collection techniques in the form of questionnaires. This research was conducted at the Antara Public Health Center, Makassar City. This research was conducted in June 2021 by distributing questionnaires to 58 respondents or the public according to the criteria. The results of this study indicate that the evaluation of diabetes patient compliance in taking diabetes mellitus medication at the Makassar City Public Health Center obtained a percentage of adherence, namely 80.09%, so that it is included in the high compliance level category.